Experience report of a mental health care in an emergency care unit (Research, Society and Development, 2020)
The objective was to report the interdisciplinary care of a mental health case that occurred in an emergency care unit. This article is an experience report on the work developed by two PET-Health/Interprofessionality preceptors who work in an emergency care unit, located in the interior of Minas Gerais, in the face of a mental health case. The methodology used was bibliographic research and experience reporting. This is a descriptive report of retrospective and innovative experience because it makes it possible to go through the theme of interprofessionality, added to the considerations about the care and care offered to mental health patients in the city. It is perceived the importance of careful looking at issues involving mental health, because they present situations that involve suffering, misadjustments, anxieties, difficulties in finding solutions or following guidelines.